Inulin characterization from tuber of Musa balbisiana Colla as an alternative source of prebiotics - In-In Hanidah; Siti Nurhasanah; Sumanti Debby Moody; Yuli Andriani; Karina Patricia (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Inulin is a polysaccharide composed of 2-60 fructose monomers linked by β-(2,1) glycosidic bonds, with a glucose end group. The tuber of Musa balbisiana Colla (batu banana) is a part of the M. balbisiana Colla plant that contains dietary fiber 6,20%. The polysaccharide content allowed the batu banana tubers to contain inulin. The aim of this study was to determine the characteristics of inulin in batu banana tubers. The research method used was the experimental method, which was analyzed descriptively with two replicates at the Universitas Padjadjaran Laboratory of Jatinangor – Sumedang from May until October 2023. The parameters were inulin content, degree of polymerization (DP), reducing sugar content, moisture content, pH, solubility, water activity (aw), color L*, a*, and b*, viscosity, and sensory analysis using a descriptive method. The results showed that B. tuber inulin had an inulin content of 3,58%, DP of 2,8, reducing sugar content of 2,03%, moisture content of 8,47%, pH of 6,31, solubility of 21,70% (90°C), aw of 0,432, L* of 66,76, a* of 8,28, b* of 15,90, and viscosity of 2068 mPas (90°C). In conclusion, sensory analysis showed that batu banana tuber inulin has a darker color, bitter taste, stronger flavor, and softer texture than the commercial inulin.